Anthropometric data for biomechanical hand model - Lee, Kyung Sun; Jung, Myung Chul; Mo, Seung Min; Min, Seung Nam (Advances in Intelligent Systems and Computing, 2019)
The aim of this study was to investigate the anthropometric data for the segment masses, center of mass (COMs) of the segments of inertia, and radii of gyration are required for the development of the biomechanical hand model. The segment masses were calculated on the basis of the segment volume using a density of 1.1 g/cm3. The segment volume was estimated from the measured length between the participants’ distal and proximal joints (segment length) and the diameters of their knuckles. The COMs for the proximal and middle segments and the distal segment were determined by approximating the phalanx by the frustum of a cone and a cylindrical homogeneous rigid body, respectively. The diameters of the knuckles were measured for each participant. We assume that they have a uniform density. The moments of inertia of the proximal and middle segments were determined by approximating the phalanx as the frustum of a conical homogenous rigid body. The diameters of the knuckles were measured for each participant. The moments of inertia of the distal segments were determined by approximating the phalanx as a cylindrical rigid body. The radii of gyration, Kx, Ky, and Kz, of the segment about the x axis, y axis, and z axis are defined as Pytel and Kiusalaas. This information will be provide useful data for development of biomechanical hand model.
Keywords: Anthropometric data; Center of mass; Hand model; Moments of inertia; Proximal joints; Rigid body; Segment lengths